The boomer revolution [videorecording (DVD)] - Ridout, Sue; Butler, Caroline; MacDonald, Ann-Marie, 1958-; Dychtwald, Ken, 1950-; Flatman, Barry (Dreamscape Media, LLC, 2017)
In the '60s, baby boomers changed the world. In their 60s, they just may do it again. The largest and wealthiest generation ever born is now leading a massive shift in what it means to get old. Boomers, who make up almost a third of Canada's total population, are now in their 50s and early 60s, but are enjoying a longevity bonus because life expectancy has gone up more than thirty years in the last century. What will they do with their extra years?